Komparative Pengaruh Dominan Current Ratio dan Debt To Equity Rasio terhadap Return On Assets pada Perusahaan Kosmetik yang terdaftar di Bursa Efek Indonesia Tahun 2012-2016 - Rina Milyati Yuniastuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The financial statements are very useful for decision making, throug financial statement information can be predicted what will happen to the company in the future. The purpose of this study is to determine the most dominant influence between current ratio and Debt to Equity ratio to return on Assets on cosmetics companies listed on the Stock Exchange. Long term contribution in research to provide information about the dominant influence between current ratio and debt to equity ratio to return on assets which is useful for the investors. Method used in this research is documentation method, that is research which use data collecting method by looking at report finance. The result of this research is Current ratio has more dominant influence to ROA compared to Debt to Equity ratio to ROA. Keywords: Dominant Influence, Current ratio, Debt to Equity ratio, Return on Assets